2021
DOI: 10.1371/journal.pone.0245603
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy of mutagenesis of gamma-irradiation in plant height and days to maturity through expression analysis in rice

Abstract: Introduction of semi-dwarfism and early maturity in rice cultivars is important to achieve improved plant architecture, lodging resistance and high yield. Gamma rays induced mutations are routinely used to achieve these traits. We report the development of a semi-dwarf, early maturing and high-yielding mutant of rice cultivar ‘Improved White Ponni’, a popular cosmopolitan variety in south India preferred for its superior grain quality traits. Through gamma rays induced mutagenesis, several mutants were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
6
12
0
Order By: Relevance
“…Mutation breeding has a unique position in breaking the bottleneck of germplasm resources. Thought to create more beneficial resources than cross-breeding, it confers higher yields in rice (Tiwari et al, 2018;Kato et al, 2020;Andrew-Peter-Leon et al, 2021). Induced mutations are valuable sources of genetic variability (Oladosu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation breeding has a unique position in breaking the bottleneck of germplasm resources. Thought to create more beneficial resources than cross-breeding, it confers higher yields in rice (Tiwari et al, 2018;Kato et al, 2020;Andrew-Peter-Leon et al, 2021). Induced mutations are valuable sources of genetic variability (Oladosu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Reports stated gamma rays had created mutants tolerant to abiotic stress, such as salinity and drought-tolerant mutants in rice (Song et al, 2012;Joshi et al, 2016;Huang et al, 2019). Further reports said variations in terms of different agronomic traits, such as plant height, tiller number, shoot and root weight, total biomass, and panicle length, occurred due to γ-irradiation (Oladosu et al, 2014;Joshi et al, 2016;Sharifi, 2019;Kato et al, 2020;Andrew-Peter-Leon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier study, we identified that WP-22-2 was highly sensitive to gibberellin ( Supplementary Material 4 ) compared with IWP (Andrew-Peter-Leon et al, 2021 ) ( Figure 2 ). Therefore, the effect of the exogenous application of GA 3 (50 μM) was studied through foliar spray on WP-22-2.…”
Section: Resultsmentioning
confidence: 85%
“…Earlier, we reported the high sensitivity of WP-22-2 to 50 µM gibberellic acid (Andrew-Peter-Leon et al, 2021). This was tested by raising WP-22-2 along with IWP (wild-type) in a completely randomized design and spraying the 10-day-old seedlings with 50 µM of GA 3 .…”
Section: Exogenous Application Of Gibberellic Acid and Expression Profiling By Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation